Răspuns :
4x+5y-6x+7y+5x-6y= 3x+6y=3(x+2y).....
2x+3x-6-2x^2+2x+6= -2x^2+7x. Sper ca te.am ajutat!
(2x+3)*(x-2) -2(x ²-x-3)= 2x-4x+3x-6-2x²+2x+3= 2x ² +3x-3.
2x ² +3x-3=0
Discriminantul = b ² - 4ac = 3 ² - 4*2*-3= 9+ 24 = 33
×₁ = [tex] \frac{-b- \sqrt{discriminant} }{2a} [/tex]= [tex] \frac{-3 \sqrt{33} }{4} [/tex].
x₂ = [tex] \frac{-3+ \sqrt{33} }{4} [/tex]
Sper ca te-am ajutat. daca discriminantul era un patrat perfect era sa fie mai usor
2x ² +3x-3=0
Discriminantul = b ² - 4ac = 3 ² - 4*2*-3= 9+ 24 = 33
×₁ = [tex] \frac{-b- \sqrt{discriminant} }{2a} [/tex]= [tex] \frac{-3 \sqrt{33} }{4} [/tex].
x₂ = [tex] \frac{-3+ \sqrt{33} }{4} [/tex]
Sper ca te-am ajutat. daca discriminantul era un patrat perfect era sa fie mai usor